2020
DOI: 10.1016/j.jtumed.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Determining the correlation between olive oil consumption, BMI, and waist circumference in the adult Saudi population

Abstract: Objective This study aimed to explore the correlation between dietary intake of olive oil, body mass index (BMI), and waist circumference (WC). Methods In this cross-sectional study, we recruited 200 participants aged 20–30 years using pre-determined inclusion and exclusion criteria. Demographic data was collected via a questionnaire, while dietary data was collected for two days using a 24-hour dietary recall. Anthropometric data such as BMI and WC were collected, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Furthermore, only 33% and 42% of participants consumed optimal amounts from fruit and vegetables, respectively [ 33 ]. Another cross-sectional study conducted on 200 Saudi adults assessed olive oil consumption from 24-h recall and the average olive oil consumption was 19 g/day for men and 17 g/day for women, which equates to 1.2 and 1.1 table spoon, respectively [ 44 ]. Previous studies on adults from Saudi and Kuwaiti population confirmed low consumption from fruit and vegetables (below five serving per day) [ 45 , 46 ], while the Omani population showed adequate intake from fruit but not from vegetables [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only 33% and 42% of participants consumed optimal amounts from fruit and vegetables, respectively [ 33 ]. Another cross-sectional study conducted on 200 Saudi adults assessed olive oil consumption from 24-h recall and the average olive oil consumption was 19 g/day for men and 17 g/day for women, which equates to 1.2 and 1.1 table spoon, respectively [ 44 ]. Previous studies on adults from Saudi and Kuwaiti population confirmed low consumption from fruit and vegetables (below five serving per day) [ 45 , 46 ], while the Omani population showed adequate intake from fruit but not from vegetables [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combined action of MUFA and polyphenol components on different metabolic pathways may contribute positively to control lipid metabolism, favor good glycemic control, and ensure good anti-inflammatory activity. Table 1 summarizes the main studies on the direct effect of OO intake on metabolic studies [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even though OO has shown a positive correlation with BMI and waist circumference, AlKhattaf et al (2020) did not identify such a relationship in a cross-sectional investigation using a Saudi adult cohort [ 26 ]. However, high OO consumers who had a significantly higher caloric intake, had a similar BMI compared to low OO consumers, indicating that OO consumption may play a role in body weight maintenance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, EVOO is also an important hallmark of the Mediterranean diet (MedD), known to have cardio-protection effects, in which its consumption is known to be inversely associated with the risk of stroke and coronary heart disease [13]. Additionally, the phenolic content of EVOO will affect cholesterol lipoproteins differently depending on its composition [5,14], such as serum lipid profiles, decreasing LDL-cholesterol, and increasing HDL-cholesterol [15], as well as modulating age-related HDL-cholesterol levels [16], all of which are important modifiable risk factors for CVD [17]. In addition, the consumption of EVOO was shown to improve postprandial glucose [18], lower the risk of diabetes, ameliorate metabolic and inflammatory biomarkers [19,20], and decrease gestational diabetes in pregnant women [21].…”
Section: Introductionmentioning
confidence: 99%